Cirurgia bariátrica e qualidade de vida de trabalhadores da saúde - Santos, Ligia Pedrosa dos (2018)
Obesity is one of the fastest growing chronic noncommunicable diseases in the world, affecting more than a third of world's population, consider a pandemic. As an alternative to overcome obesity, it is observed that bariatric number surgeries have increased, mainly by achieving faster personal satisfaction. The aim was to comprehend impacts of bariatric surgery on quality of life of health workers in Uberlândia county (MG). We developed triangulation of methods getting data by means of individual semistructured interviews, questionnaire of socio-economic characteristics and World Health Organization Quality of Life Questionnaire (WHOQOL-Bref). Participated in the study 14 health professionals submitted to surgery bariatric. Sample was obtained by snowball technique. An analysis of the WHOQOL-Bref showed that professionals evaluated their quality of life as good (64.3%) or very good (35.7%), revealed excellent levels of satisfaction and good repercussions on daily activities, work and self-image after surgery. Significant concern about weight maintenance and weight regain has been noted especially in people who have had surgery longer, differing from those who have undergone surgery recently.